Técnicas de selección de personal (2019)
In this monograph we talk about a very difficult topic in the organizations worldwide and reaching more to the point in Colombia, where to find the talent suitable for a position of use becomes tedious and sometimes a little difficult to handle. All this is because we do not have the study and the BTS selection techniques to get to find the best candidate either external or internal. This work counts a bit of how to arrive step by step to find the best talent since the recruitment, followed by the selection, where we will have some techniques like the interview, psych technical tests, professional tests, etc. ". And finally the hiring, for this issue should be done before a study and description of the role in which we identify the problems that this position and how we can improve it with a person fit for problem solving, where , you will have to have a fair wage, bonuses according to the degree of complexity of the position, good quality of life, often have training, induction and to make this person successful within the company and all their studies and improvements process Commentator make the organization grow.